Mobile phones and the “commercialisation” of relationships: expressions of masculinity in Southern Mozambique - Archambault, J (Syracuse University Press, 2012)
“Nowadays, relationships are more commercialised”, explained Antonio, a 22 year-old Mozambican who had recently broken up with his girlfriend, “if you don't phone back when a girl sends you a bip, she'll run to another guy.” As he recalled the events that lead to their break-up, Antonio used mobile phone etiquette as an idiom to express his understanding of contemporary gender relations. In Mozambique, many people have passed “from no phone to [mobile] phone” (Orlove 2005: 699) and the recent integration of telecommunication into everyday life has opened up new spaces and possibilities. Despite generating great enthusiasm, however, the phone is also understood to challenge power relations between men and women, as well as between generations. Indeed, although few would do without their phone, many are rather ambivalent in their evaluation of this new technology. In this chapter, I look into the integration of mobile phones into courtship practices amongst young adults in Inhambane, Southern Mozambique. I argue that while reproducing gendered ideals, mobile phone etiquette acts as a new register to express and address the reconfiguration of gender relations and the redrawing of ideas of masculinity already underway.